Forming of serpentine micro-channels on SS304 and AA1050 ultra-thin metallic sheets using stamping technology. (August 2020) - Sudarsan, Coomar; Sajun Prasad, K; Hazra, Sumit; Panda, Sushanta Kumar
Abstract: The present work explored the application of conventional stamping technology to manufacture micro-channels in SS304 and AA1050 ultra-thin sheets of 200 μm thickness. In order to obtain defect free stamped components, the forming limit diagrams (FLDs) of both the ultra-thin sheets were determined experimentally by sub-sized stretch forming setup, and these were further used as diagnostic tool for formability predictions. The finite element (FE) simulation of the stamping process was performed to predict different channel parameters such as channel width, depth and thinning development. Based on these predicted results, an in-house stamping test setup was designed and developed to fabricate novel multi-pass and parallel-serpentine micro-channels, and the stamping operation was demonstrated successfully using a 20 ton hydraulic press. The micro-channels with an average width of 1.5 mm and depth of 0.463 mm were fabricated without any wrinkling and fracture, and moreover, the quality of the channels was investigated in terms of channel depth uniformity, thinning development and surface roughness. It was observed that uniform channel with a negligible variation of approximately 1.5% in depth was observed at the central channel compared to that of the lateral channel irrespective of the material. The thickness distribution showed a maximum thinning of approximately 23% and 11% near the bottom corner region of the channels in case of AA1050 and SS304 ultra-thin sheets respectively. Also, surface roughness was found to be higher in the micro-channels fabricated using AA1050 material compared to that of SS304 material due to larger initial grain size and higher amount of effective plastic strain in AA1050 material during stamping.